2017
DOI: 10.12659/msm.898535
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Acupuncture Against Gentamicin-Induced Ototoxicity in Rats: Possible Role of Neurotrophin-3

Abstract: Background:The aim of this study was to investigate the protective effects of acupuncture against gentamicin-induced ototoxicity and explore the possible protective role of neurotrophin-3 (NT-3). Material/Methods:Twenty-four rats were divided randomly into 4 groups: control group, gentamicin group, neitinggong group, and tinggong group. Rats in the gentamicin, neitinggong, and tinggong groups received intraperitoneal injection of gentamicin (100 mg/kg) for 14 consecutive days. Rats in the neitinggong and tingg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Our results showed also that gentamycin is middle in its cochlear toxicity. Similar result was seen by other authors where average threshold value of ABR was significantly higher in the gentamicin group as compared with that of the control group [23] animal model established by Okuda et al [24] showed that moderate damage of inner ear occur with moderate-dose of gentamycin. The effect of intraperitoneal gentamicin ototoxicity on the cochlea of the rats was studied with auditory brain stem responses (ABRs), and histopathological investigation [21].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results showed also that gentamycin is middle in its cochlear toxicity. Similar result was seen by other authors where average threshold value of ABR was significantly higher in the gentamicin group as compared with that of the control group [23] animal model established by Okuda et al [24] showed that moderate damage of inner ear occur with moderate-dose of gentamycin. The effect of intraperitoneal gentamicin ototoxicity on the cochlea of the rats was studied with auditory brain stem responses (ABRs), and histopathological investigation [21].…”
Section: Discussionsupporting
confidence: 87%
“…Various studies could be found dealing with the morphology of the stereocilia of the hair cells following aminoglycosides toxicity [19][20][21][22][23][24]. However, there was no detailed description of the stereocilia of the normal hair cells.…”
Section: Discussionmentioning
confidence: 99%